The influence of communication, image and perceived value on customer satisfaction and brand loyalty: a study on gsm operators - Durgut, Muammer (My University, 2010)
Bugünün rekabetçi piyasasında tüm firmalar pazar paylarını artırabilmek için tüketicilerini etkileyebilecek farklı stratejileri araştırmaktadır. Bu durumda tüketiciler satınalma kararını vermeden önce ürünlerle ilgili çok çeşitli bilgi arasından kendi ihtiyaç ve isteklerine en uygun ürünü seçimde zorlanabilmektedir. Fakat marka sadakati satış kararını etkileyen önemli etkenlerden birisidir. Bu nedenle sadık müşterilerin varlığı uzun ve sürdürülebilir iş ortamı oluşturma açısından oldukça önemlidir. Marka sadakatini tetikleyici faktörlerin bilinmesi kurumlara, müşterilerine daha doğru yaklaşım stratejileri geliştirme fırsatı verecektir. Bu tezin amacı cep telefonu operatörlerine yönelik marka sadakatini sağlayan ve müşterilerin GSM operatörü seçimini belirleyen etkenleri bulabilmektir. Bu çalışmada ayrıca müşterileri sadakat yönünde güdüleyen faktörler detayları ile de incelenmiştir. Bu çalışma GSM operator sektöründeki pazarlama uzmanları için önem arz etmektedir. Marka sadakatini oluşturan faktörleri öğrenmek pazarlama stratejilerini belirlemeye yön vermeyi sağlayacaktır. Ayrıca çalışmada test edilen model marka sadakatinin diğer sektörlere etkisi açısından da yönlendirici olacaktır. Bu amaçlarla yapılan saha çalışmasının sonucunda bütünleşik pazarlama iletişimi, müşteri ilişkileri yönetimi, kalite ve fiyat algısı marka sadakatini oluşturan belirgin etkenler olarak bulunmuştur. Marka Sadakati, Müşteri Memnuniyeti, GSM operatorü

In today’s competitive market, all companies are searching for different strategies to attract more customers in order to increase their market share. Thus customers are faced with much information that makes it difficult for them to choose the one that fits their needs and wants best, before giving their final purchase decision. However, brand loyalty is one of the significant factors that affect purchase decision; hence it is important for the companies to have loyal customers in order to build a long-term, sustainable business environment. Knowing about the motivating factors behind brand loyalty will provide the organizations the opportunity to develop their strategies with a more customer focused approach. This study aims and helps us to understand the underlying motivating factors for the choice of a GSM operator which lead to brand loyalty in mobile phone operators. Moreover, the study tries to explain the motivating factors for brand loyalty in detail. This study is important for the marketers of the companies in GSM operators sector, because outlining the factors that constitute brand loyalty will give directions to the marketers while determining their marketing strategies. Moreover, the model that is tested in this study will give directions to other sectors in terms of brand loyalty. For these aims, a field study has been done with various mobile phone users. As a result of this field study, it is found out that integrated marketing communication (IMC) activities, customer relation management (CRM) activities, perceived quality and perceived price are the motivating factors that lead to brand loyalty. Key Words: Brand Loyalty, Customer Satisfaction, GSM operator
Keywords: Pazarlama; Rekabet; Üretim Yönetimi